Stress-Driven Production of γ-Aminobutyric Acid Using Non-Conventional Yeast Strains Kluyveromyces marxianus JMY140K and Metschnikowia reukaufii JMY075 - Ting-Ting Fan; Chao Chen; Du-Wen Zeng; Feng-Lou Wang; Zhao-Xian Xu; Ming-Jie Jin; Yue Zou; Jun Li; Xin-Qing Zhao (Journal of Fungi)
γ-Aminobutyric acid (GABA) is a valuable amino acid widely used in food, healthcare, and agriculture. GABA bioproduction by budding yeasts has been commonly reported, but related studies using non-conventional yeasts remain limited. In this study, two non-conventional natural yeast strains, namely, Kluyveromyces marxianus JMY140K and Metschnikowia reukaufii JMY075, were identified as promising GABA producers, and M. reukaufii JMY075 was discovered to be a GABA producer. Enhanced GABA production was observed in the two yeast strains under stress conditions, including high temperature and high ethanol and acetic acid levels. In particular, K. marxianus JMY140K showed 7.93 times higher GABA titers under thermal stress than that of the control. External stress conditions significantly influenced the GABA production of these two yeast strains. The culture filtrate of K. marxianus JMY140K also showed promising activities in human skin cells. In addition, K. marxianus JMY140K could also produce GABA using rice straw hydrolysate, which indicated that it has the potential to produce GABA using renewable biomass. Our studies provide insight for further enhancing the GABA production of natural yeasts and promoting its biotechnology applications.